Modeling syntactic complexity with P systems: A preview - Enguix, Gemma Bel; Nagy, Benedek (Springer Verlag service@springer.de, 2014)
Membrane systems have been applied to several branches of linguistics, taking advantage of their possibilities when describing contexts and environments. However, not much research has been performed in the field of modeling syntax. The paper introduces a preliminary approach to syntactic complexity using the basic operations of membranes. © 2014 Springer International Publishing Switzerland.
13th International Conference on Unconventional Computation and Natural Computation, UCNC 2014 --
Keywords: Artificial intelligence; Computer science; Computers; Basic operation; Membrane system; P systems; Preliminary approach; Syntactic complexity; Syntactics